Realizing Sustainable Development Goals (SDGs) by Reviving Mosque Functions in Family Guidance - M. Ilham Muchtar; Muktashim Billah (Journal of Family Law and Islamic Court, 2022)
Mosques have a great deal of potential for supporting Muslim families. However, there are still a lot of mosques that do not fully utilize this excellent opportunity. In order to shed light on this issue, a literature review titled " Realizing Sustainable Development Goals (SDGs) by Reviving Mosque Functions in Family Guidance" was conducted. The problem stated in this paper is "How to revive the mosque's role in family formation." This study seeks to explain the idea of creating a Muslim family centered around a mosque. The methodology utilized is qualitative, and the literature or books that are relevant to the topic of the conversation are used as data sources. This study demonstrates that by maximizing mosques' contributions to the development of Muslim households, helping the government achieve the Sustainable Development Goals (SDGs), especially those that relate to a healthy, prosperous living and high-quality education. Re-actualizing mosque management and congregational coaching techniques is important to maximize the mosques' contribution to the upbringing of Muslim families. The management side comes first; every mosque needs a mission and vision that are both distinct and measurable. Particularly when it comes to achieving one of the most crucial tasks, which is the development of Muslim families. Mosques should offer more welcoming facilities for the congregation. so that parents can watch events at the mosque in safety and comfort. Next: elements of the coaching approach For the purpose of making the guidance materials more efficient, organized, and focused on the desired vision, a guidance on guidance materials is required. These resources cover several facets of faith, worship, and muamalah in addition to tazkiyatun nafs and other resources. The following techniques are utilized to put the notion into practice: lectures, question-and-answer sessions, group discussions, demonstrations, assignments, and field trips. -- Masjid memiliki potensi sangat besar dalam pembinaan keluarga muslim berbasis masjid. Namun masih banyak masjid yang tidak memanfaatkan potensi besar tersebut. Maka untuk mengungkap persoalan tersebut dilakukan penelitian pustaka dengan judul “Revitalisasi Fungsi Masjid dalam Pembinaan Keluarga Mewujudkan Tujuan Pembangunan Berkelanjutan (TPB)”. Rumusan masalah dalam penelitian ini adalah “Bagaimana revitalisasi fungsi masjid dalam pembinaan keluarga”. Penelitian ini bertujuan untuk mendeskripsikan konsep pembinaan keluarga muslim berbasis masjid. Metode yang dipakai adalah kualitiatif dengan sumber data yang digunakan berupa buku-buku atau literatur yang berkaitan dengan pembahasan. Penelitian ini menunjukkan bahwa; optimalisasi peran masjid dalam pembinaan keluarga muslim berbasis masjid, mendukung pemerintah dalam mewujudkan Tujuan Pembangunan Berkelanjutan (TPB)/Sustainable Development Goals (SDGs), khususnya pada aspek kehidupan sehat dan sejahtera, dan pendidikan berkualitas. Guna optimalisasi peran masjid dalam pembinaan keluarga muslim perlu dilakukan reaktualisasi pada aspek manajemen masjid dan metode pembinaan jamaah: Pertama: aspek manajemen, yakni setiap masjid seyogyanya mempunyai visi dan misi yang jelas dan terukur. Terutama dalam pembinaan keluarga muslim sebagai salah satu misi penting yang akan dicapai. Masjid hendaknya memiliki fasilitas yang lebih friendly dengan para jamaahnya. Sehingga orang tua merasa aman dan nyaman mengikuti kegiatan di masjid. Kedua: aspek metode pembinaan, diperlukan adanya Panduan Materi Pembinaan sehingga lebih efektif, sistematis dan terarah sesuai visi yang dituju. Materi-materi dimaksud meliputi aspek akidah, ibadah dan muamalah serta tazkiyatun nafs dan materi lainnya. Adapun metode yang dipakai dalam implementasi konsep dimaksud antara lain; metode ceramah, metode tanya jawab, metode diskusi, metode demosntrasi, metode penugasan dan metode karya wisata.